Proposal for Academic Achievement and Permanence of Students in the 7th Grade (1) - Miranda Calderón, Luis Alfredo (2011)
This paper analyzes the impact of change processes experienced by many student populations when completing primary education (1st-6th grade) and starting secondary education (7th-11th grade). Based on the research conducted, this paper describes situations and aspects that may result in conditional factors for the student’s adjustment at this level: time-space changes, as well as organizational and dynamic changes that would set the new educational environment and social context in which this new stage will be developed. Such conditional factors that affect learning in incoming students: programs, teaching methodology, learning styles and new evaluation methods will be discussed. As a result of this research, a proposal is presented to facilitate transition from primary to the secondary education. This proposal includes guidelines for awareness and strengthening of pedagogical mediation, which would contribute to the permanence of students from all types of institutions in the education system.   (1) [Translator’s note: The Costa Rican education system is composed of primary education (1st-6th grade) and secondary education (7th-11th grade).]